Sport Careers and Process of Career Termination - Wysoczański-Minkowicz, Rafał (Sport and Tourism Central European Journal, 2024)
The main objectives of this article are: to discuss the problem of retirement among professional athletes and to develop recommendations for a pension system dedicated to athletes. The issue of retirement in sport is complex because of the specific nature of professional sports persons’ occupation and its multi-layer ramifications for life after the sports career. The retirement process differs for athletes versus other members of society because they have to finish careers when their bodies do not allow them to perform at the expected level, at a relatively young age in comparison to other occupations. As a result, they face multiple challenges, such as embarking on a new career path. The article includes a description of the athletic career, touching upon issues such as the necessity for early and narrow specialization. Subsequently, challenges connected with athletes’ retirement are presented in the light of both the sociological and psychological perspective. Institutional solutions designed to make a post-career transition are also discussed. This article is based on the existing literature from the field and review of programmes established to facilitate athletes’ retirement process. The paper may be considered a contribution to a discussion oneffective ways to facilitate athletes’ retirement process.